1981
DOI: 10.1099/00221287-126-1-63
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Outer Membrane Proteins in the Survival of Neisseria gonorrhoeae P9 within Guinea-pig Subcutaneous Chambers

Abstract: Guinea-pig subcutaneous chambers were infected with a mixture of gonococcal variants of defined outer membrane protein profile. Survival within the chambers was a two-stage process. The initial advantage conferred by the lack of opacity-related outer membrane protein was transient and survivors were replaced by opaque colonial variants. Amongst these survivors were variants which produced opacity-related proteins (IId, IIe and IIf) not present in the initial inoculum. Thus, outer membrane protein composition i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1982
1982
1999
1999

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…We believe that all eight or nine P,ll genes are probably functional, despite the fact that our screening of colony variants revealed the existence of only six P,ll proteins (Barritt ef at., 1987), There may be multiple P,ll proteins not distinguishable by the criteria we used in screening. Alternatively, expression of some P.ll proteins may be favoured only under specific growth conditions, such as those found in vivo (McBride et at., 1981).…”
Section: Discussionmentioning
confidence: 99%
“…We believe that all eight or nine P,ll genes are probably functional, despite the fact that our screening of colony variants revealed the existence of only six P,ll proteins (Barritt ef at., 1987), There may be multiple P,ll proteins not distinguishable by the criteria we used in screening. Alternatively, expression of some P.ll proteins may be favoured only under specific growth conditions, such as those found in vivo (McBride et at., 1981).…”
Section: Discussionmentioning
confidence: 99%
“…The surface components of gonococci have been under vigorous investigation in attempts to expand our knowledge about the biology of this organism and to find potential vaccine antigens for gonorrhea. Most antigens studied to date exhibit extensive structural and antigenic variations, e.g., pili (10,19,22), protein I, the major outer membrane protein with porin function (15,31,35), the heat-modifiable proteins II, which are associated with colony opacity (5,13,40), and lipopolysaccharide (1). In contrast, protein III exhibits a conserved structure (16) yet induces blocking antibodies that interfere with the bactericidal effects of other specific antibodies (26).…”
mentioning
confidence: 99%
“…Recent work has shown that even in a single strain surface antigens are capable of considerable variations in vitro (Swanson, 1978; and probably in vivo (James & Swanson, 1977;McBride et al, 1981). Colonial variants of the same strain have been shown to produce pili with altered morphology and subunit molecular weight (Penn et al, 1980;Salit et al, 1980), which show differences in their attachment to epithelial cells (Lambden et al, 1981 b).…”
Section: Introductionmentioning
confidence: 99%